HANDGRIP STRENGTH AND SOME RELATED FACTORS AMONG OLDER PATIENTS WITH OSTEOPOROSIS - Nguyen, Thi Thu Huong; Nguyen, Ngoc Tam; Tran, Viet Luc (Tạp chí Sinh lý học Việt Nam, 2023)
<div class="@w-sm/main:[scrollbar-gutter:var(–stage-scroll-gutter)] touch:[scrollbar-width:none] group/scroll-root relative flex min-h-0 min-w-0 flex-1 flex-col [scrollbar-gutter:stable] not-print:overflow-x-clip not-print:overflow-y-auto group-data-stream-active/scroll-root:[overflow-anchor:none] not-print:data-expanded-composer:overflow-y-hidden! scroll-pt-(–header-height) [–sticky-padding-top:var(–header-height)] [–sticky-padding-bottom:0px] [–scroll-root-safe-area-inset-top:calc(var(–sticky-padding-top)+env(safe-area-inset-top,0px))] [–scroll-root-safe-area-inset-bottom:calc(var(–sticky-padding-bottom)+var(–screen-keyboard-height,0px)+env(safe-area-inset-bottom,0px))] [–scroll-root-safe-area-height:calc(100lvh-var(–scroll-root-safe-area-inset-top)-var(–scroll-root-safe-area-inset-bottom))] has-data-[fixed-header=less-than-md]:md:scroll-pt-0 has-data-[fixed-header=less-than-md]:md:[–sticky-padding-top:0px] has-data-[fixed-header=less-than-xl]:@w-xl/main:scroll-pt-0 has-data-[fixed-header=less-than-xl]:@w-xl/main:[–sticky-padding-top:0px] has-data-[fixed-header=less-than-xxl]:@w-2xl/main:scroll-pt-0 has-data-[fixed-header=less-than-xxl]:@w-2xl/main:[–sticky-padding-top:0px] group-data-[side-pane-shell-open]/side-pane-shell-host:[scrollbar-width:none] group-data-[side-pane-shell-open]/side-pane-shell-host:[&::-webkit-scrollbar]:hidden" data-scroll-root="" data-scroll-from-top=""> <main id="main" class="not-keyboard-focused:outline-none min-h-0 flex-1" tabindex="-1"> *]:pointer-events-auto R6Vx5W_threadScrollVars scroll-mb-[calc(var(–scroll-root-safe-area-inset-bottom,0px)+var(–thread-response-height))] scroll-mt-[calc(var(–header-height)+min(200px,max(70px,20svh)))]" dir="auto" data-turn-id="request-WEB:35aba3d2-fd98-4613-9705-72e325ca48bf-4" data-turn-id-container="request-WEB:35aba3d2-fd98-4613-9705-72e325ca48bf-4" data-testid="conversation-turn-10" data-turn="assistant"> <div class="text-base my-auto mx-auto pb-10 [–thread-content-margin:var(–thread-content-margin-xs,calc(var(–spacing)*4))] @w-sm/main:[–thread-content-margin:var(–thread-content-margin-sm,calc(var(–spacing)*6))] @w-lg/main:[–thread-content-margin:var(–thread-content-margin-lg,calc(var(–spacing)*16))] px-(–thread-content-margin)"> <div class="[–thread-content-max-width:40rem] @w-lg/main:[–thread-content-max-width:48rem] mx-auto max-w-(–thread-content-max-width) flex-1 group/turn-messages focus-visible:outline-hidden relative flex w-full min-w-0 flex-col agent-turn" data-conversation-screenshot-content=""> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal outline-none keyboard-focused:focus-ring [.text-message+&]:mt-1" dir="auto" tabindex="0" data-message-author-role="assistant" data-message-id="dd0bdd59-8680-4d8e-8c22-d93cccd76a74" data-message-model-slug="gpt-5-5" data-turn-start-message="true"> Objectives: To assess handgrip strength (HGS), lower limb strength, and some related factors among older people with osteoporosis. Subjects and Methods: A cross-sectional study was conducted on 141 older patients with osteoporosis examined and treated at National Geriatric Hospital from June to October 2022. HGS was measured using a handgrip strength dynamometer, and lower limb strength was assessed by the 5-time chair stand test. General information, characteristics of osteoporosis, and geriatric syndromes were collected. Results: Overall, 56% of participants had impaired HGS, and 24.8% had impaired lower limb strength. Older age was significantly associated with lower HGS (p<0.05). Participants with impaired HGS had a lower mean body mass index (BMI) (p<0.05). The prevalence of lumbar spondylosis and diabetes differed significantly between participants with and without impaired HGS (p<0.05). Individuals who experienced pain and lumbar spine deformity had a higher prevalence of impaired HGS (p<0.05). Cognitive decline increased the risk of HGS impairment by 5.7 times. In addition, the risk of HGS impairment was higher among participants with low physical activity (OR=3.9), sleep disturbance (OR=3.8), depression (OR=3.7), frailty syndrome (OR=3.5), risk of falls (OR=3.4), and malnutrition (OR=2.2). Conclusion: Half of the study participants had reduced HGS, and one-quarter had reduced lower limb muscle strength. Age, BMI, diabetes, lumbar spondylosis or other joint diseases, living status, and geriatric syndromes were significantly associated with impaired HGS. </main> <dialog class="group/dialog @container inset-0 min-h-full min-w-full whitespace-normal items-center justify-center overflow-auto overscroll-y-contain bg-[rgba(0,0,0,0.5)] backdrop-blur-[1px]"></dialog> <audio class="fixed start-0 bottom-0 hidden h-0 w-0" crossorigin="anonymous" autoplay="autoplay"></audio>